2014
DOI: 10.1589/jpts.26.865
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Joint Immobilization and Remobilization in the Rats

Abstract: [Purpose] The purpose of our study was to clarify temporal effects on restrictions to range of motion and the histopathological changes of joint components after joint immobilization in a rat knee-contracture model. [Subjects] Fifty-four male Wistar rats were randomly divided into two groups: a fixation group, and a control group. [Methods] In the fixation group, unilateral knee joints were immobilized at full flexion using a plaster cast for 4 weeks. At four weeks the animals were randomly divided into six su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 11 publications
(12 reference statements)
3
18
0
1
Order By: Relevance
“…While many studies report improved cartilage repair in defects positioned in the trochlear over the femoral condyle (Orth et al 2013a ), conflicting results, where less defect repair occurs in the trochlea compared to the medial condyle have also been reported (Hoemann et al 2011 ; Hoemann et al 2005 ). In the clinical scenario most operators will follow surgery with a 4–6 week period of partial-weight bearing with full range of motion in the joint, slowly working up to full weight bearing (Vogt et al 2013 ) even though short term studies have shown an accelerated rehab protocol can reduce pain and increase function (Vogt et al 2013 ; Ebert et al 2008 ) In the preclinical in vivo model weight bearing can be controlled by using external fixators and casts on the animals (Kojima et al 2014 ; Roth et al 1988 ). Confining animals to pens for the initial post-operative period has been shown to be effective in reducing post-operative joint load (Etterlin et al 2014 ).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…While many studies report improved cartilage repair in defects positioned in the trochlear over the femoral condyle (Orth et al 2013a ), conflicting results, where less defect repair occurs in the trochlea compared to the medial condyle have also been reported (Hoemann et al 2011 ; Hoemann et al 2005 ). In the clinical scenario most operators will follow surgery with a 4–6 week period of partial-weight bearing with full range of motion in the joint, slowly working up to full weight bearing (Vogt et al 2013 ) even though short term studies have shown an accelerated rehab protocol can reduce pain and increase function (Vogt et al 2013 ; Ebert et al 2008 ) In the preclinical in vivo model weight bearing can be controlled by using external fixators and casts on the animals (Kojima et al 2014 ; Roth et al 1988 ). Confining animals to pens for the initial post-operative period has been shown to be effective in reducing post-operative joint load (Etterlin et al 2014 ).…”
Section: Reviewmentioning
confidence: 99%
“…Post-operative rehabilitation of cartilage repair in humans varies from centre to centre, it has been shown free movement and gradual increase in weight bearing improves outcomes, however, this is complex to ensure in animal models (Nishino et al 2010 ; Assche et al 2011 ). When using an in vivo model casts can be used to immobilise rat limbs (Kojima et al 2014 ; Maldonado et al 2013 ), however it is more common in large animals such as goats and sheep to keep them in small pens in the immediate post-operative period (Marmotti et al 2013 ) to limit their mobilising. In some animals, such as horses, non-weight bearing is impossible, and can cause severe life-threatening illnesses.…”
Section: Operative Factors Influencing Model Selectionmentioning
confidence: 99%
“…One study by Trudel et al separately analyzed the recovery of myogenic and arthrogenic contractures following remobilization, and found that arthrogenic contracture progressed as a result of joint remobilization, following short‐term immobilization (less than 4 weeks). There are some studies reporting histological changes in joint capsules during remobilization, but the changes responsible for the remobilization‐induced aggravation of arthrogenic contracture have not yet been identified. Michelson and Hunneyball observed the development of inflammation in the immobilized joint capsules of rabbits, and found that subsequent remobilization further aggravated the synovitis.…”
mentioning
confidence: 99%
“…The heads of the animals are also fixed with a metal loop over the neck region to restrict head movements (9). Currently, immobilization stress can also be induced by fixing the limbs of the animal in an adjustable plastic bag, a transparent plexiglass cylinder or other equipment (12,23,24). Restraint stress is generally performed by keeping the animals in small wire mesh cages, a cylindrical or semi-cylindrical tube with ventilation holes for a stipulated period of time (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%